Evaluation of Ecological Service Function in Cotton‐Based Multiple Cropping Systems - Chun‐yan Chang; Jia‐rui Deng; Fei Liu; Xin‐dong Liu; Jun‐ke Wu; Min Gao; Xiao‐yi Liang; Zhuo Li (Food and Energy Security)
ABSTRACT Double cropping in cotton fields is a prominent agricultural practice in the Yellow River basin, enhancing yields and overall cotton production benefits. However, there is limited research on the agronomic performance and long‐term ecological sustainability of cotton‐based cropping systems. This study evaluates the ecological service functions of various cotton‐based cropping systems, focusing on crop productivity and ecological security. Field experiments were conducted to examine the dynamics of insect pest and natural enemy populations, soil nutrients, agricultural investment, and economic benefits across different cropping systems, including monoculture cotton with (MC1) or without chemical pesticides (MC2), garlic‐cotton rotation with (GC1) or without chemical pesticides (GC2), wheat‐cotton rotation with (WC1) or without chemical pesticides (WC2), and cotton‐garlic intercropping with (CG1) or without chemical pesticides (CG2) in Jinxiang and Shanxian. The results showed that garlic‐cotton rotation significantly improved species richness, conserved natural enemies, and enhanced economic benefits (GC1: +692.99%; GC2: +692.40%) compared to other systems. However, wheat or garlic rotation without pest control significantly decreased soil organic matter. Overall, garlic‐cotton rotation proved to be a sustainable and efficient cropping system for traditional cotton‐growing areas in the Yellow River basin, providing theoretical and technical support for environmentally friendly cotton production in China.